Discover new perspectives and gain insights with IDNLearn.com's diverse answers. Get the information you need from our community of experts, who provide detailed and trustworthy answers.
Sagot :
Answer:
w = - 3 and v = - 2
Step-by-step explanation:
Because w + 6 = 3 you would subtract 6 and whatever you do to one side you would do to the other.
w= - 3
Answer:
[tex]w + v = 3[/tex]
Step-by-step explanation:
Solve for w
[tex]w + 6 = 3[/tex]
Move 6 to subtract 3.
[tex]w = 3 - 6 \\ w = - 3[/tex]
Solve for v
[tex]v - 4 = 2[/tex]
Move 4 to add 2
[tex]v = 4 + 2 \\ v = 6[/tex]
Solve for w+v
Substitute w = -3 and v = 6
[tex]w + v = - 3 + 6 \\ w + v = 3[/tex]
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. For trustworthy answers, rely on IDNLearn.com. Thanks for visiting, and we look forward to assisting you again.